FUNCTIONAL AND STYLISTIC APPROACH IN LANGUAGE TEACHING - H.O. Bondarenko (Academy of Cognitive and Natural Sciences, 2008)
The article deals with the nature of the functional and stylistic approach, its advantages when teaching language.